“Just a second, mommy’s here”: the impact of mothers’ smartphone use on children’s affect regulation and the quality of mother–child interactions - Mikić, Aleksandra; Bergmann, Sarah; Perejoan Martí, Georgina; Klein, Annette M. (Frontiers in Psychology, 2025)
IntroductionThe ubiquity of smartphone devices in our everyday lives has been widely recognized as a potential challenge to the quality of parent–child interactions. The aim of this study was to experimentally examine the effects of mothers’ smartphone use on their children’s affect regulation and on the quality of mother–child interactions, indicated by emotional availability of the dyad and maternal responsiveness. Additionally, we investigated the associations between mothers’ behaviors to maintain contact with their children during smartphone use and their children’s affect regulation.MethodsThe experiment consisted of two counterbalanced phases: the free play phase and the interruption phase, in which mothers were replying to standardized text messages in the presence of their children. The sample comprised 52 mothers and their children aged 5 to 6 months (24 female).ResultsInfants expressed less positive affect in the interruption phase than in the free play phase, as well as more negative affect in the interruption phase when the free play phase preceded the interruption phase. In addition, the mothers showed less sensitivity and responded to less infants’ signals and in a slower way in the interruption phase than in the free play phase. Moreover, mothers showed less optimal structuring, and children showed less well involvement of their mothers in the interruption phase than in the free play phase. Lastly, more children’s negative affect was associated with a shorter duration of mothers’ smartphone use and more active mothers’ behaviors to maintain contact with their children during the smartphone use.DiscussionThese results suggest that, although mothers adapt smartphone use based on their children’s affective response, mothers’ repeated smartphone use negatively impacts their children’s affect regulation and the quality of the mother–child interactions, with potentially negative consequences for the children’s social–emotional development.